2011
DOI: 10.1007/s13157-011-0204-5
|View full text |Cite
|
Sign up to set email alerts
|

Forested Wetland Communities as Indicators of Tidal Influence along the Apalachicola River, Florida, USA

Abstract: On coastal rivers, tidal freshwater forested wetlands occur at the upriver extent of tidal influence. How far upriver is uncertain, because tidal conditions gradually diminish and it is unknown how forest species and edaphic conditions shift in response. Forested wetlands along the lower Apalachicola River were evaluated for the influence of tidal hydrology on community composition, structure, and soil conditions. A total of 37 forest plots were established along a tidal gradient and classified as tidal or non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Soil organic matter ranged from 9% to 77% with no clear pattern between alluvial and blackwater rivers. Detailed studies by Coultas (1984) and Anderson & Lockaby (2011) of tidal forest soils of the Apalachicola River, an alluvial river that drains mostly in the Piedmont region, revealed pH (5.4-6.0) and concentrations of organic C (7.5-18%) and N (0.45-0.89%) that were comparable to values measured in Altamaha and Ogeechee River soils (Table 1), and higher than those in the Satilla and S. Newport Rivers. Some tidal forest soils contained mostly sand and others such as the Apalachicola River (FL) soils contained mostly clay (Coultas, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soil organic matter ranged from 9% to 77% with no clear pattern between alluvial and blackwater rivers. Detailed studies by Coultas (1984) and Anderson & Lockaby (2011) of tidal forest soils of the Apalachicola River, an alluvial river that drains mostly in the Piedmont region, revealed pH (5.4-6.0) and concentrations of organic C (7.5-18%) and N (0.45-0.89%) that were comparable to values measured in Altamaha and Ogeechee River soils (Table 1), and higher than those in the Satilla and S. Newport Rivers. Some tidal forest soils contained mostly sand and others such as the Apalachicola River (FL) soils contained mostly clay (Coultas, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…These findings contrast with Wharton et al (1982), who found that, in non-tidal floodplain forest soils upriver, blackwater soils contained more sand than alluvial soils, similar to what I observed in tidal forest soils of the blackwater Satilla River vs. the alluvial Altamaha River. Detailed studies by Coultas (1984) and Anderson & Lockaby (2011) of tidal forest soils of the Apalachicola River, an alluvial river that drains mostly in the Piedmont region, revealed pH (5.4-6.0) and concentrations of organic C (7.5-18%) and N (0.45-0.89%) that were comparable to values measured in Altamaha and Ogeechee River soils (Table 1), and higher than those in the Satilla and S. Newport Rivers. Soil properties of our tidal forests soils generally fall within the wide ranges for organic matter, pH, and N compiled for alluvial and blackwater tidal forest soils of the southeastern Atlantic and Gulf coasts (Anderson & Lockaby, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimate of the spatial extent of tidal freshwater ecosystems is a first step toward framing the tidal extension concept as a problem to be addressed by the scientific community. However, the upriver limit of tidal freshwater forested wetlands (TFFW) is extremely difficult to map and assess because hydrologic and vegetation gradients are clear but subtle (Anderson and Lockaby ). In addition, no estimates have been made of the overall length of tidal freshwater river channels.…”
Section: Which Rivers Will Experience Tidal Extension?mentioning
confidence: 99%
“…() measured greater primary productivity of giant cutgrass ( Zizaniopsis miliacea ) in tidal freshwater marsh as compared to impounded (unrestored and formerly tidal) non‐tidal marsh. Community composition of canopy species differs between non‐tidal floodplain forest and TFFW (Anderson and Lockaby ). Smaller trees, more shrubs, more herbaceous cover, and less wood production and litterfall are found in tidal than non‐tidal freshwater floodplain forests (Brinson et al .…”
Section: How Will Tidal Extension Alter Ecosystem Functions?mentioning
confidence: 99%